The Incarcerated Christ: Crime and Prison in Karl Barth’s Life and Theology - Jobe, Sarah (The journal of theological studies, 2025)
This article argues that Karl Barth is a justice-involved theologian, someone whose own criminal record and experience in prisons have shaped his core theological commitments. The article serves as a detailed overview of Barth’s personal and professional experience in courts and prisons, but it presses beyond that treatment to show how these experiences shaped his doctrine. The article begins with how Barth’s own arrest and conviction in Germany in 1934-5 inform his concept of Jesus the Judged Judge. It turns to Barth’s decade of engagement at Basel Prison as both a relief preacher and a volunteer prison chaplain and the ways in which that engagement shaped his Christology and soteriology. The article then explores Barth’s holidays and sacramental life in prison, his development of an ethics for prison chaplains, and his tour of American prisons as a deepening of his own discipleship of a criminalized Christ. Finally, the essay concludes with an analysis of the last paragraphs of Church Dogmatics IV/4. In Barth’s final published words, he witnesses to Jesus as a convicted and incarcerated God who accomplishes salvation history in prison.